VARIABILITAS TINGKAT KETERSERAPAN FE BERAS ANTAR VARIETAS PADI VARIABILITY IN BIOAVAILABILITY OF FE IN RICE VARIETIES - , Suwarto; , Nasrullah; , Taryono; Sulistyaningsi, Endang (Pembangunan Pedesaan, 2009)
Many papers have reported that Fe deficiency caused anemia is a worldwide problem. It has also been reported that most of the Fe intake of people came from cereals. To improve Fe nutrition of rice consumers, grain Fe concentration must not only be increased, but it must also be in a form that available to consumers of rice. This study set out to determine the bioavailability of Fe in rice of 10 varieties. Results indicated that bioavailability of rice grain Fe varied among different varieties. Three varieties (Maligaya Sp., Bengawan Solo, and Gilirang) had a higher Fe bioavailability than the standard of IR 64. There was no correlation between bioavailability of Fe and grain Fe concentration in rice grain.